2018
DOI: 10.1016/j.tins.2018.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Respiration-Entrained Brain Rhythms Are Global but Often Overlooked

Abstract: We revisit recent evidence showing that nasal respiration entrains oscillations at the same frequency as breathing in several regions of the rodent brain. Moreover, respiration modulates the amplitude of a specific gamma sub-band (70-120Hz), most prominently in frontal regions. Since rodents often breathe at delta and theta frequencies, we caution that previous studies on delta and theta power and their cross-regional synchrony, as well as on delta-gamma and theta-gamma coupling, may have detected the respirat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
306
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 267 publications
(328 citation statements)
references
References 74 publications
20
306
1
1
Order By: Relevance
“…We also demonstrated that nasal respiration can modulate inter‐cortical coherence at γ frequency, especially between remote neocortical areas. This evidence suggests that the respiratory rhythm could facilitate inter‐regional communication (Tort et al., ; Zhong et al., ). Previously described γ synchrony between areas of the brain as a dynamical mechanism for the control of cross‐regional information flow and integration process (Fries, , ; Singer, ; Womelsdorf et al., ) could be part of a larger phenomenon, which includes respiratory modulations.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…We also demonstrated that nasal respiration can modulate inter‐cortical coherence at γ frequency, especially between remote neocortical areas. This evidence suggests that the respiratory rhythm could facilitate inter‐regional communication (Tort et al., ; Zhong et al., ). Previously described γ synchrony between areas of the brain as a dynamical mechanism for the control of cross‐regional information flow and integration process (Fries, , ; Singer, ; Womelsdorf et al., ) could be part of a larger phenomenon, which includes respiratory modulations.…”
Section: Discussionmentioning
confidence: 97%
“…In the present study, we demonstrated the existence of CFC between the phase of the respiratory wave and the amplitude of γ oscillation in the cat neocortex. It is important to note that the average frequency and limits of the γ burst differ between species (Herrero et al., ; Rojas‐Líbano et al., ; Tort et al., ; Zelano et al., ) vary according to the animal's alertness level (Rojas‐Líbano et al., ) and to the recording site (Karalis & Sirota, ). In addition, we showed that this coupling remains intact during the carbachol‐induced cataplexy, which strongly suggests that the muscular tone is not involved in this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Respiration has been observed to exhibit phase synchronization to stimulus presentation in another study (Huijbers et al, ), and recent research (Yackle et al, ) has shown that removal of respiratory pattern generator (cahedrin‐9) pre‐Botzinger neurons reduces arousal in mice, possibly via termination of the connection from this respiratory pattern generator to the LC. A commentary on this finding further suggested that respiration could affect arousal, and perhaps cognition, via the LC (Sheikhbahaei & Smith, ), and a very recent study has observed coupling between respiration and fluctuations of electrical activity in rodent brains (Tort, Brankack, & Draguhn, ). Stimulus‐locked respiratory phase has further been shown to affect perception of fear and the encoding of memory (Zelano et al, ), and respiration exhibits coupling with frontal theta activity (Stankovski et al, ), which is inversely related to DMN activity (Braboszcz & Delorme, ; Scheeringa et al, ).…”
Section: Initial Research Findingsmentioning
confidence: 96%
“…In addition, hippocampal SWRs are now known to be coordinated with essentially the entire brain (Logothetis et al, ) (Kaplan et al, ; Ramirez‐Villegas, Logothetis, & Besserve, ). Intriguingly, both low‐frequency rhythms and SWRs have also recently been shown to relate to non‐neural physiology with global influence (respiration; Liu, McAfee, & Heck, ; Lockmann & Tort, ; Tort, Brankack, & Draguhn, ). Studies at the level of neural firing have moreover identified interregional coordination of representations relevant to task behaviors (e.g., (Jadhav, Rothschild, Roumis, & Frank, ; Ji & Wilson, ; Pennartz, Ito, Verschure, Battaglia, & Robbins, ; Peyrache, Khamassi, Benchenane, Wiener, & Battaglia, ; Pezzulo, van der Meer, Lansink, & Pennartz, ; Rothschild, Eban, & Frank, ).…”
Section: Three Brain States In Cortexmentioning
confidence: 99%